ISOLASI DAN KARAKTERISASI BAKTERI PENAMBAT NITROGEN NON-SIMBIOTIK TANAH GAMBUT CAGAR BIOSFER GIAM SIAK KECIL-BUKIT BATU - RAHEL KABURUAN; HAPSOH HAPSOH; GUSMAWARTATI GUSMAWARTATI (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2014)
Giam Siak Kecil Biosphere-Bukit Batu (GSK-BB) is Riau peatlands area which is largest composed by lowland peat swamp forest ecosystem. Seeing peatland ecosystem getting extreme, there will be small possibility that soil microbes are able to breed optimally, but microbes in tropical land has not been explored. However, the high content of organic matter, allowing soil microbial activity in the organic matter recycle that essential to life such as nitrogen cycle. Non-symbiotic nitrogen fixing bacteria is a free-living bacteria and plays a role in the supply of N in the soil. The results of the isolated and characterization of single bacterial isolates obtained 31 non-symbiotic N fixing of GSK-BB peat Biosphere which allegedly largest to genus Azotobacter, Azospirillium and Clostridium pasteurianum as well as the results of clear zone isolates on the medium modification, from the single isolates contained 14 isolate that potentially in a non-symbiotic N with the largest ratio of clear zone obtained HTA1 10-4 NS-2, HTA1 10-4 NS-1, HTA 4 10-4 NA-1 dan HTA5 10-4 NS-2.